Salam And Istishna Sale Practices In The Modern Economic Era: Scholars’ Perspectives In Sharia Economic Law Analysis - Dea Dahlia; Henni Rahayu Handayani; Dwi Sri Handayani; Catur Galuh Ratnagung (Consensus : Jurnal Ilmu Hukum, 2026)
This study examines the transformation of salam and istishna transactions in contemporary Islamic economic practices, particularly in relation to the application of khiyar rights. While classical jurisprudence recognizes various forms of khiyar, modern transactions tend to emphasize khiyar al-‘aib, with khiyar al-majlis becoming less applicable due to spatial separation and limited direct interaction. Using a qualitative literature-based approach, this research analyzes classical and contemporary scholarly perspectives on the implementation of these contracts. The novelty of this study lies in its focus on the shift in khiyar application within modern transactional contexts and its implications for Sharia compliance. The findings indicate that salam and istishna transactions remain permissible as long as they meet essential legal requirements, including clear product specifications, agreed pricing, and defined delivery terms. However, practices involving unfair conditions, such as non-refundable payments upon cancellation, contradict Sharia principles and are therefore prohibited.